Problems of Islamic education: Analysis of philosophical perspectives - Mutmainah, Siti; Supriyanto, Supriyanto; Amrin, Amrin (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
This research explores educational issues in the context of the study of Islamic educational philosophy. Involving classical traditions to modern adaptations, this philosophical reflection details the conflict between traditional values and the demands of the times. The challenges are not only conceptual, but also practical, such as aligning religious teachings with modern educational needs. This research method uses an educational qualitative approach through literature study to explain problems in the study of Islamic educational philosophy. The discussion includes the basic ideas, objectives, functions and urgency of Islamic educational philosophy, as well as the concept of education in madrasas. Solutions to the problem include strengthening the curriculum, policy direction for madrasa development, and scientific integration. In closing, the issues of ontology, epistemology and axiology in Islamic education are studied, describing the dynamics of Divine and Human values as well as educational methods from the perspective of Islamic educational philosophy.